Foley Catheterization Versus Oral Misoprostol for Induction of Labour in Hypertensive Women in India (INFORM): A Multicenter, Open-label, Randomized Controlled Trial. Issue 2 (June 2018) - Mundle, S.; Bracken, H.; Khedikar, V.; Mulik, J.; Faragher, B.; Easterling, T.; Leigh, S.; Granby, P.; Haycox, A.; Turner, M.A.; Alfirevic, Z.; Winikoff, B.; et al.
Abstract : ( Lancet . 2017;390(10095):669–680) Hypertensive disorders, including preeclampsia, affect 10% of all pregnancies, with preeclampsia and eclampsia accounting for roughly 14% of global maternal deaths annually. While treatment with magnesium sulfate or antihypertensive drugs can reduce maternal morbidity and mortality, the best preventive method is timely vaginal delivery. Low-dose oral misoprostol and the Foley catheter are 2 low-cost cervical ripening methods recommended for use in low-resource settings, where most morbidity and mortality associated with preeclampsia occurs. However, few studies have compared these 2 methods directly. The INFORM trial aimed to compare the efficacy, safety, acceptability, and cost-effectiveness of labor induction via oral misoprostol versus Foley balloon catheter in women with gestational hypertension in a low-resource setting.